2006
DOI: 10.1074/jbc.m508191200
|View full text |Cite
|
Sign up to set email alerts
|

Paratope Determination of the Antithrombotic Antibody 82D6A3 Based on the Crystal Structure of Its Complex with the von Willebrand Factor A3-Domain

Abstract: Platelet adhesion, activation, and aggregation are the three major steps in primary hemostasis, a process that is necessary for the cessation of bleeding at sites of vascular injury. The same process is also responsible for pathologic thrombus formation, particularly in arteries at sites of high shear stress. At high shear stress, binding of von Willebrand factor (VWF) 3 to collagen that is exposed in the subendothelial matrix after injury, and the subsequent interaction of the immobilized VWF with the plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The bilayer interaction site of the VWF A3 domain was tested by mapping NMR signal perturbations obtained upon titration with DHPC micelles (Supplementary Figure 1) onto the crystal structure (Staelens et al 2006). This demonstrates a complicating role of conformational flexibility, as it suggests that the C-terminal α -helix of this domain is displaced upon detergent interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The bilayer interaction site of the VWF A3 domain was tested by mapping NMR signal perturbations obtained upon titration with DHPC micelles (Supplementary Figure 1) onto the crystal structure (Staelens et al 2006). This demonstrates a complicating role of conformational flexibility, as it suggests that the C-terminal α -helix of this domain is displaced upon detergent interaction.…”
Section: Resultsmentioning
confidence: 99%
“…near the collagen-binding site (2,3,6,12). The β3-α2 loop includes residue W1745 that has been suggested to play a direct role in collagen binding (13,14).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is generally accepted that VWF binds to collagen via its A3 domain. Detailed studies using recombinant A3 domain [104] or monoclonal antibodies against the A3 domain [105] have shown that both these strategies are capable of inhibiting platelet adhesion to collagen under high shear conditions and, under some circumstances platelet aggregation to collagen. Additional data from a variant von Willebrand's disease Type IIb patient point to a possible (indirect?)…”
Section: Gpib Complex As a Collagen-binding Site On Plateletsmentioning
confidence: 99%